Attitudes, commitment and motivation amongst Icelandic elite athletes - Halldorsson, V.; Thorlindsson, T. (Annual meeting of the American Sociological Association Annual Meeting, Caesar's Palace, Las Vegas, NV, Aug 19, 2011, 2011)
The aim of the research was to test whether elite-level athletes differ from second-level athletes on socio-psychological measures such as commitment and motivation in relation to their success. Questionnaire data was retrieved from all Icelandic elite athletes at the time of the study (n=50), using non-elite athletes as controls (n=64). The elite athletes scored higher than the control group on all items on the Commitment Rating Scale (CRS) and on most items on The Motive to Achieve Success Scale (MASS). Women tended to score higher than men. Our findings further indicate that athletes seem to attribute their success in sport to socio-psychological attributes rather than physical and innate ones. We argue that in order to gain a more comprehensive understanding of the factors that shape athletic excellence, future studies will need to address social and psychological factors as well as biological ones.